2017
DOI: 10.7307/ptt.v29i4.2362
|View full text |Cite
|
Sign up to set email alerts
|

Unified Tanker Survey and Inspection Regime in Terms of Reducing Psychophysical Strain of the Crew

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…From the analysis presented in this paper and the results obtained in the previous research [16], it can be concluded that there is a need and possibility to improve safety regime for oil tankers. Apart from the extensive annual inspection duration, the intensity and time of execution, usually in ports during intensive activity analysed in our previous research [16], there is another aspect that should be taken into account. Costs of numerous inspections are paid by shipowners and contribute to a significant level of expenditures to comply with maritime regulations [17].…”
Section: Suggestion For Improvementmentioning
confidence: 61%
See 2 more Smart Citations
“…From the analysis presented in this paper and the results obtained in the previous research [16], it can be concluded that there is a need and possibility to improve safety regime for oil tankers. Apart from the extensive annual inspection duration, the intensity and time of execution, usually in ports during intensive activity analysed in our previous research [16], there is another aspect that should be taken into account. Costs of numerous inspections are paid by shipowners and contribute to a significant level of expenditures to comply with maritime regulations [17].…”
Section: Suggestion For Improvementmentioning
confidence: 61%
“…Costs of these inspections, obtained from experts or found on websites are given in Table 1. Furthermore, a detailed analysis of the surveyed components of all regimes has shown that a significant number of components (69%) are examined by all regimes [16]. Moreover, results of the previous research indicated that such overlapping and inspection durations and intensity can cause unnecessary psychophysical strain of the crew [16].…”
Section: Suggestion For Improvementmentioning
confidence: 98%
See 1 more Smart Citation
“…During inspection of oil tanker 282 items, related to certification, safety management and the operator's procedures manuals, survey and repair history, enhanced survey programme, condition assessment scheme, crew management, crew qualifications, drug and alcohol policy, navigation policies, procedures and documentation, navigation equipment, charts and publications, navigation, safety management, drills, training and familiarisation, ship security, enclosed space and pump room entry procedures, monitoring non-cargo spaces, gas analysing equipment, hot work procedures, life-saving equipment, fire-fighting equipment, material safety data sheets, access, oil record books, shipboard oil and marine pollution emergency plans, VOC management plan, cargo operations and deck area pollution prevention, pump rooms and oil discharge monitors, ballast water management, engine and steering compartments, garbage management, energy efficiency, structural condition, cargo and ballast systems policies, procedures and documentation, stability and cargo loading limitations, cargo operations and related safety management, cargo and ballast handling and monitoring equipment, ullaging, sampling and closed operations, venting arrangements, inert gas system, crude oil washing, static electricity precautions, manifold arrangements, pump rooms, cargo hoses, cargo lifting equipment, ship to ship transfer operations, mooring equipment documentation, mooring procedures, mooring equipment, anchoring equipment, single point moorings, emergency towing arrangements, communications procedures, communications equipment, engine and steering compartments policies, procedures and documentation, planned maintenance, safety management, machinery status, steering compartment, hull, superstructure and external weather decks, electrical equipment, internal spaces and accommodation areas are carefully and critically examined. Taking into account time needed to check all afore mentioned components, requirements to discuss any observation with the member of the shipʹs staff assigned to accompany the inspector and the inspection findings with the Master or the Masterʹs authorised deputy before leaving the vessel, vetting inspection usually lasts 10 h. [1] Considering comprehensiveness of the VIQ, properly conducted inspection by competent inspector, as enabled and assured by SIRE, should be sufficient as a part of the screening process. However, it seems that a number of oil companies do not use SIRE system as it was intended and requires additional SIRE inspections although tanker has a report that is less than 6 months old.…”
Section: Oil Tanker Vetting Inspectionmentioning
confidence: 99%
“…Research show that because scope and extent of tanker inspections significantly overlap, they are in certain extent redundant, and such over-inspection may have a negative effect on the psychophysical condition of the crew. [1] Additionally, it has been shown that over-inspection does not necessarily decrease the probability of having a casualty but can rather increase it. [4] Moreover, we estimate that average price of inspections is at least 33600 USD per oil tanker.…”
Section: Oil Tanker Vetting Inspectionmentioning
confidence: 99%